(untitled) (Praxis Educativa, 2024)
The advance in educational inclusion has visualized the presence of deaf students with their own culture and language in regular education establishments. At the national and international level, a series of educational devices have been created for the acquisition of the vehicular language of migrant students, which from a socio-anthropological perspective has not been visualized for the deaf educational community. The objective of this article is to propose a device for deaf students in educational establishments. As a result, through a theoretical analysis, a Hospitality Device for Deaf Students (DIHOPES) is proposed with 4 dimensions: Culture of Hospitality, Welcome Protocols, Specialized Professionals and Language Immersion Classroom. As a reflection, the articulation of the dimensions of this device is based on the principle of hospitality and the acceptance of deaf otherness that seeks to be recognized as part of the educational community.